Teoria kontroli społecznej jako jedna z teorii dewiacji - Rydzewski, Paweł (Wydział Prawa i Administracji UAM, 1989)
The article contains an attempt to present the achievements of the social control theory as one of the theories of deviation. The social control theory was created by sociologists and criminologists in the USA m the 1950s and 1960s. It was one of the forms of reaction to a drastic increase in crime rates in the USA around that period. Its founders were A. J. Reiss, W. С. Reckless,, D. Matza, J. Toby, F. I. Nye, T. Hirschi. A basic assumption of this theory is that deviation is a natural, spontaneous reaction to the weakening or disappearance of social control. Unlike the socialization theory, the social control theory does not assume the existence of additional deviation norms assimilated through learning. Theer basic types of social control can be distinguished: 1. group control (performed by family, small groups and institutions and based on social norms internalized due to strong emotional ties with the group); 2. system control (performed indirectly by the whole social and culturalsystem; some features of the system may be conductive to the appearance of deviation); 3. personal control (internal control performed by an individual and based on internalized social norms and on some personality traits). Two versions of the social control theory can be distinguished. While a „classic" version is based on the assumption of natural character of deviation, a .,modified" version points to factors motivating towards deviation. The most promising would be a „modified" version that would allow for the influence of the socialization theory. An advantage of the social control theory is the possibility of its wide use in praxis, especially in the form of preventive activities.
Social control theory as one of the theories of deviation